2020
DOI: 10.1016/j.jcbs.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological flexibility mediates the relations between acute psychedelic effects and subjective decreases in depression and anxiety

Abstract: Prior research has shown that acute subjective psychedelic effects are associated with both spontaneous and intended changes in depression and anxiety. Psychedelics are also theorized to produce increases in psychological flexibility, which could explain decreases in depression and anxiety following a psychedelic experience. Therefore, the present cross-sectional survey study sought to examine whether psychological flexibility mediated the relationship between acute psychedelic experiences and spontaneous or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
223
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(245 citation statements)
references
References 57 publications
20
223
0
2
Order By: Relevance
“…The observation that blissful ego-dissolution is followed by long-term reductions in psychopathology, greater well-being, and increased openness may thus, at least in part, be explained in terms of reduced avoidance. In line with this idea, a recent survey study (91) found that the impact of acute mysticaltype effects on decreases in depression and anxiety after naturalistic psychedelic use was entirely mediated by increases in psychological flexibility (a construct that is closely related to acceptance). Some positive effects of ego-dissolution could nonetheless be relatively unrelated to acceptance [e.g., see (92)].…”
Section: Examining the Role Of Ego-dissolution Experiencesmentioning
confidence: 91%
“…The observation that blissful ego-dissolution is followed by long-term reductions in psychopathology, greater well-being, and increased openness may thus, at least in part, be explained in terms of reduced avoidance. In line with this idea, a recent survey study (91) found that the impact of acute mysticaltype effects on decreases in depression and anxiety after naturalistic psychedelic use was entirely mediated by increases in psychological flexibility (a construct that is closely related to acceptance). Some positive effects of ego-dissolution could nonetheless be relatively unrelated to acceptance [e.g., see (92)].…”
Section: Examining the Role Of Ego-dissolution Experiencesmentioning
confidence: 91%
“…More recently, two studies (18,32) examined the relationship between improved mental health following psychedelic use and decreases on the revised Acceptance and Action Questionnaire [AAQ-II; (33)], a frequently used measure of both experiential avoidance and psychological flexibility. Both studies found that psychedelic use was associated with post-psychedelic decreases in AAQ-II scores (18,32). Furthermore, Close et al (32) found that, following psychedelic use, decreased AAQ-II scores were associated with decreases in depression severity.…”
Section: Experiential Avoidance As a Potential Transdiagnostic Mechanismmentioning
confidence: 99%
“…Furthermore, Close et al (32) found that, following psychedelic use, decreased AAQ-II scores were associated with decreases in depression severity. Additionally, Davis et al (18) found that decreased AAQ-II scores indirectly affected the relationship between acute psychedelic experiences (mystical-type experiences and psychological insight) and decreases in anxiety and depression severity. Importantly, however, extant research suggests that the AAQ-II shows poor discriminant validity from psychological distress (34)(35)(36)(37)(38).…”
Section: Experiential Avoidance As a Potential Transdiagnostic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Mystical‐type and insight experiences as measured using validated questionnaires were found to be highly correlated with one another while only indirectly correlated with improved psychological well‐being. Regression analyses showed mystical‐type and insight experiences to be highly correlated with improved psychological flexibility and feelings of personal meaningfulness which in turn were highly correlated with improved psychological outlook (Davis, Barrett, & Griffiths, 2020; Garcia‐Romeu et al, 2019; Garcia‐Romeu et al, 2020). Therefore, these studies suggest that it is the improved psychological flexibility and personal meaningfulness associated with mystical‐type and insight experiences which enables depressed and anxious individuals and people with substance use disorders to reframe how they view their medical conditions, themselves, their lives and relationships with others (Belser et al, 2017; Davis et al, 2020; Garcia‐Romeu et al, 2019, 2020; Spiegel, 2016; Watts, Day, Krzanowski, Nutt, & Carhart‐Harris, 2017).…”
Section: Mechanistic Understandingmentioning
confidence: 99%